Epidemiological Distribution and Reinfection Status: A Cross Sectional Study of COVID-19 Patients in Makwanpur District, Nepal - Karki, Supendra; Khadka, Hari Bahadur; Dahal, Aashma; Bhandari, Keshav Raj; Shrestha, Binika; Ghimire, Laxman; Aryal, Nishan; Tiwari, Dipak Prasad; Prachhai , Deepak Bahadur (International Journal of Silkroad Institute of Research and Training, 2025)
Background: The second wave of COVID-19 in Nepal showed increased infectivity and case fatality compared to the first wave, mirroring global trends. Despite the nationwide vaccination campaign initiated in February 2021, breakthrough infections and reinfections remained a public health concern. This study aimed to assess the epidemiological distribution of COVID-19 cases and evaluate reinfection patterns in relation to vaccination status in Makwanpur district, Nepal. Method: A cross-sectional study was conducted involving individuals diagnosed with COVID-19 between May 15 and August 15, 2022. Data collection commenced in July 2022 using a systematic sampling technique. A total of 377 participants who were in home isolation during the study period were interviewed via telephone using a pretested, paper-based questionnaire. Result: Among the 375 participants, 56.8% were female and 65.9% were Brahmin/Chettri. Asymptomatic cases constituted 83.8% of the sample. Twenty-three participants (6.1%) reported reinfection. Of the 210 vaccinated individuals, only 134 (65%) were fully vaccinated. Vero cell was the most administered vaccine (39.5%). A statistically significant association was observed between gender and vaccination status (p-value < 0.001), and between vaccination status and symptom presentation (p-value=0.007), with vaccinated individuals more likely to be asymptomatic. No significant associations were found between reinfection and vaccination status (p-value = 0.29), nor with age group (p-value = 0.42). Conclusion: While vaccination appeared to reduce symptomatic cases, reinfection occurred regardless of vaccination status. These findings highlight the need for continued surveillance and further research into the long-term effectiveness of COVID-19 vaccines, especially in the context of emerging variants.